Weak and Strong Forms of Ï‰-Perfect Mappings - Ashaea, G. S.; Yousif, Y. Y. (Iraqi Journal of Science, 2020)
In this paper, we introduce weak and strong forms of Ï‰-perfect mappings, namely the ï±-Ï‰-perfect, weakly ï±-Ï‰-perfect and stronglyï±-Ï‰-perfect mappings. Also, we investigate the fundamental properties of these mappings. Finally, we focused on studying the relationship between weakly ï±-Ï‰-perfect and stronglyï± -Ï‰-perfect mappings.